"It's not yet a gift": understanding digital gifting - Kwon, Hyosun; Koleva, Boriana; Schnädelbach, Holger; Benford, Steve (2017)
A myriad of digital artifacts are routinely exchanged online. While previous studies suggest that these are sometimes considered to be gifts, CSCW has largely overlooked explicit digital gifting where people deliberately choose to give digital media as gifts. We present an interview study that systematically analyzes the nature of digital gifting in comparison to conventional physical gifting. A five-stage gift exchange model, synthesized from the literature, frames this study. Findings reveal that there are distinctive gaps in people’s engagement with the digital gifting process compared to physical gifting. Participants’ accounts show how digital gifts often involve less labor, are sometimes not perceived as gifts by the recipient and are rarely reflected on and reciprocated. We conclude by drawing out design implications for digital gifting services and rituals.